A DEFENCE OF A MINIMALIST ACCOUNT OF COSMOPOLITAN JUSTICE (2016)
Cosmopolitan justice, the view that justice is a universal idea that should apply to all persons irrespective of nationality has generated a lot of debate among political philosophers. Earlier studies have conceived of justice either as a territorially-bounded concept or as a trans-territorial idea, which must apply globally but failed to provide a trans-culturally persuasive account of justice that would form the basis for regulating transnational relations. This study, therefore, developed an account of cosmopolitan justice founded on the minimum requirement of non-harm that would provide a trans-culturally persuasive basis for regulating relations among nations. The study adopted aspects of Kant’s categorical imperative which emphasised respect for persons as framework. Eight major texts on political philosophy and moral philosophy including Miller’s On Nationality (ON), Beitz’s Political Theory and International Relations (PTIR), Jone’s Global Justice (GJ) and Pogge’s World Poverty and Human Rights (WPHR), O’Neill’s Bounds of justice (BJ), Kant’s Groundwork of the Metaphysics of Morals (GMM), Norman’s The Moral Philosophers(MP) and Singer’s Practical Ethics (PE) were purposively selected. These works dealt extensively with the question of the proper scope of justice. Conceptual analysis was used to clarify key concepts such as justice, minimalism and non-harm while the critical method was employed to examine earlier approaches to trans-national understanding of justice and to develop a minimalist account of cosmopolitan justice. Texts on political philosophy revealed the nature of the dispute between cosmopolitans who argue that principles of justice must be extended to the global arena while anti-cosmopolitans perceive justice as applicable only within national borders. Cosmopolitans claim that the level of institutional ties that bind societies across the world are morally significant and that the recognition of basic rights to a minimally decent existence is a basis for cosmopolitan justice (PTIR, WPHR and GJ). Against this view, anti-cosmopolitans contend that justice is a context-dependent norm that is only applicable amongst co-nationals who share special associational bonds (ON). Text on moral philosophy stressed the importance of moral equality of persons which imposes on us the duty of beneficence and non-harm as core ethical principles that ought to regulate our interactions with others (GMM and PE). Critical intervention shows that the approaches`` of earlier cosmopolitans and anti-cosmopolitans were inadequate on account of their rigid emphasis on institutional and associational ties. In the contemporary world the consequences of our actions increasingly affect distant others. Paying particular attention to duty of non-harm owed all persons and the phenomenon of transnational harm, the principle of justice remains relevant to individuals who do not belong to a common nationality or institutional scheme. The principle of non-harm thereby provides a more persuasive basis for evolving a theory of justice that will be cross-culturally relevant. Causal responsibility for harm is sufficient to trigger the obligation of justice within and across nations. A minimalist account of cosmopolitan justice founded on the principle of non-harm, therefore, provides adequate basis for regulating transnational relations